The future of the history of psychology in Argentina and Brazil - Klappenbach, Hugo Alberto Arturo (2016)
This article analyzes the development of the history of psychology in Argentina and Brazil, beginning with the emergence of the history of psychology at the beginning of the 20th century. The paper analyzes that such old historical reconstructions were written by the same authors or institutions that were introducing Psychology in the two countries. That is, the older historical productions in the field of psychology were Whig biased. An analysis of the last 30 years of history of psychology is also provided. The article describes institutional developments, including archives, journals, scientific meetings, and teaching of history of psychology in academic settings. Main groups devoted to history of psychology, both in Argentina and Brazil are described. Finally, it offers some thoughts on the future of history of psychology in the 2 countries. A comparative study between Argentina and Brazil allows to understand strengths and weakness related to institutionalization of History of Psychology.